STRATEGI PENINGKATAN MUTU STANDAR PROSES PEMBELAJARAN MATEMATIKA - Pulungan, Lilik Hidayat (Hijri, 2022)
Process Standards are national education standards relating to the implementation of learning in educational units to achieve graduate competency, applicable to primary and secondary education levels in the formal school, both in the package system and in the semester credit system. Furthermore, through articles 19 to 22 concerning Educational Process Standards that the learning process in educational units is carried out interactively, inspiring, fun, challenging, motivating students to participate actively, and providing sufficient space for initiative, creativity and independence according to talents, interests and the physical and psychological development of students, the existence of exemplary educators, the existence of effective and efficient planning, implementation, and supervision in the assessment of the learning processKeywords:Quality Strategy, Process Standards, Math Teacher